Students’ Perception on the Use of ChatGPT as a Language Learning Tool - Abd Rahim, Mia Emily; Abd Rahim, Emma Marini; Razawi, Nurul Amilin; Mohamed, Nuruladilah (Idealogy Journal; Vol 8 No 2 (2023): Idealogy Journal (September 2023)DO - 10.24191/idealogy.v8i2.456, 2023)
Through the advancement of technology, specifically on Artificial Intelligence (AI), ChatGPT has emerged as one of the most significant tools of the 21st century in many areas, especially the education sector in many nations. The main objective of this study was to examine the perception of the students towards the usage of ChatGPT as a language learning tool. This study employs a quantitative study as its research design, involving 181 students from various faculties and campuses in Universiti Teknologi MARA (UiTM) across several states in Malaysia that were selected as respondents to collect the data. A descriptive analysis was implemented to analyze the data obtained. Based on the result, the finding shows that most of the students think that the use of ChatGPT helps to improve their ability specifically in writing and the students also think that the use of ChatGPT makes English Language learning more enjoyable and engaging. Keywords: Technology, Education, ChatGPT, Artificial Intelligence, Language Learning.